Metal complexes of poly(iminoethylene) modified with dithiocarbamate and poly(iminoethylene) compounded with montmorillonite as flame retardant systems for polypropylene - Nour, M. A. (Polimery, 2022)
This study is focused on the assessment of metal complexes of poly(iminoethylene) modified by dithiocarbarnate compounded with montmorillonite and poly(iminoethylene) interchelated with montmorillonite as flame retardant materials for polypropylene. The assessment process is based on a comparative study of the results obtained using cone calorimeter at 35 kW/m(2) and thermogravimetric analysis (TGA). The comparative study revealed that the fire performance index (FPI) increased in the order: POZ8 > POZ2 > POZ3 > POZ1 > POZ4 as it is abbreviated in the text. Good agreement with these results was obtained from the char yield results using thermogravimetric analysis.